2016
DOI: 10.1111/eff.12325
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblage dynamics in an intermittent river of the northern Australian wet–dry tropics

Abstract: Intermittent rivers make up a large portion of the global river network and are the dominant river type in northern Australia. Increased pressure is being placed on such systems, and a better understanding of their ecology is needed. We examined, over a 7‐year period, the fish fauna of the intermittent Fergusson River, a major tributary of the Daly River of the northern Australia. Changes in habitat structure with the onset of the dry season involved contraction of the riffle/run/pool habitat to a single refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
(79 reference statements)
1
21
0
Order By: Relevance
“…This is similar to values observed in other Mediterranean‐climate systems (Magalhâes et al, ; Pires et al, ; Vardakas et al, ) and semiarid systems (Arthington, Balcombe, Wilson, Thoms, & Marshall, ; Beesley & Prince, ), but much lower than the fish species richness documented from intermittent streams in the wet–dry tropics (e.g. 20–30 species: Minshull, ; Pusey, Kennard, Douglas, & Allsop, ). The dominance of native fishes at Coyote Creek may be in large part the result of seasonal drying and habitat contraction to which non‐native species are not adapted.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to values observed in other Mediterranean‐climate systems (Magalhâes et al, ; Pires et al, ; Vardakas et al, ) and semiarid systems (Arthington, Balcombe, Wilson, Thoms, & Marshall, ; Beesley & Prince, ), but much lower than the fish species richness documented from intermittent streams in the wet–dry tropics (e.g. 20–30 species: Minshull, ; Pusey, Kennard, Douglas, & Allsop, ). The dominance of native fishes at Coyote Creek may be in large part the result of seasonal drying and habitat contraction to which non‐native species are not adapted.…”
Section: Discussionsupporting
confidence: 87%
“…By examining separate stream components based on flow intermittence and species components based on origin (native or non‐native), we exposed underlying changes in diversity patterns that would otherwise not have been apparent. We found that native species often played a greater role than non‐native species in contributing to beta diversity in intermittent streams, indicating intermittent streams represent important habitats to support local native fish persistence and contribute to maintaining regional diversity through time (Datry, Moya, Zubieta, & Oberdorff, ; Pusey, Kennard, Douglas, & Allsop, ). Fluctuations in river flow due to annual or seasonal hydrologic events (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Extremely seasonal wet season flows create an expanded array of habitat but also act as a disturbance (Stewart‐Koster et al, 2011) and can be both a source of mortality and recruitment. Pronounced intermittency, which is the dominant characteristic of most northern rivers (Kennard et al, 2010), similarly creates opportunities for recruitment while flows persist but prove inimical when they cease (Pusey, Kennard, Douglas, & Allsop, 2016). It is not without significance that northern Australia's most widely distributed fish, L. unicolor , is characteristic of intermittent streams (Pusey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%